Cytological mechanisms of unreduced pollen formation in Solanum tuberosum L. cv. Morfana - (:unkn) unknown (My University, 2002)
Bu çalışmada Solanum tuberosum L. cv. Morfana çeşidinin polen ana hücrelerinde mayoz bölünme incelendi ve şu bozukluklar görüldü: univalent ve multivalentlerin oluşumu, kromozom köprüleri, fragmentler, gecikmiş kromozomlar, yoğunlaşmış kromozomlar, tripolar dağılım. Polen ana hücrelerinin çoğunda telofaz I i sitokinez izler ve diatlar oluşur. Diat hücreleri mayoz II yi geçirmezler ve indirgenmemiş kromozomlu mikrosporları oluştururlar. Erken sitokinez ve diat oluşum yüzdeleri arasında paralellik vardır. İndirgenmemiş polen oluşumunun temel sitolojik mekanizmasının erken sitokinez olduğu sonucuna varılmıştır.

In this study, the meiotic division in pollen mother cells (PMCs) of Solarium tuberosum L. cv. Morfana was investigated and the following irregularities were observed: univalent and multivalent formation, chromosome bridges, fragments, lagging chromosomes, condensed chromosomes, tripolar separation. In majority of pollen mother cells the first telophase was followed by cytokinesis and dyads are formed. These cells do not undergo second meiotic division. As a result, unreduced microspores are produced. The frequency of premature cytokinesis corresponded well with the frequency of dyads leading to unreduced pollen formation. It was concluded that the major cytological mechanism of unreduced pollen formation is premature cytokinesis in this cultivar of potato.
Solanum tuberosum L. cv. Morfana' da indirgenmemiş polen oluşumun sitolojik mekanizmaları
Keywords: Biyokimya ve Moleküler Biyoloji